Application of DNA typing methods and genetic analysis to epidemiology and taxonomy of Saccharomyces isolates. - Clemons, K V (1997)
We have previously described differences in phenotype and virulence among clinical and nonclinical isolates of Saccharomyces. To further characterize these isolates, a comparison of restriction fragment length polymorphism (RFLP) patterns and genetic analysis were done. The cellular DNA of each of 49 clinical and 11 nonclinical isolates of Saccharomyces was digested with the endonuclease EcoRI, and the resultant fragments were separated by electrophoresis. Sixty isolates were grouped on the basis of the presence (group B) or absence (group A) of a 3-kb band. Group A contained 43 isolates (35 clinical and 8 nonclinical isolates) in 31 discernible subgroups, and group B had 17 isolates (14 clinical and 3 nonclinical isolates) in 10 subgroups. Interestingly, six of eight known vaginal isolates were group B, with four of those six being identical. Virulence of isolates was associated with membership in group A (P = 0.03). Comparison of known members of sibling species within the genus Saccharomyces, which cannot be distinguished by standard biochemical tests, showed that S. paradoxus, S. bayanus, and S. cerevisiae could be differentiated by RFLP analysis. Genetic analysis of the isolates forming viable spores showed that most group A isolates were diploid and members of the species S. cerevisiae. Those group A and B isolates unable to form viable spores may be diploid hybrids between Saccharomyces species. The group B isolates that formed viable spores were tetraploid and may also be interspecific hybrids. Overall, clinical isolates of Saccharomyces were very heterogeneous and exhibited little clonality. RFLP pattern analysis could be a useful method of demonstrating transmission in patients with infection or between environmental sources and patients.